(untitled) (Revista de Biología Marina y Oceanografía, 2019)
Peruvian grunt Anisotremus scapularis is distributed from Ecuador to Chile and it is considered an important aquaculture resource in Peru. Knowledge of embryonic development is crucial because it is part of the basic biology of a species. The aim of this study was to describe the embryonic stages of Peruvian grunt. The eggs were obtained by natural spawning and reared at 19 °C under laboratory conditions. Morphometric characteristics of the egg were evaluated: diameter (0.752 ± 0.025 mm) (mean ± sd) and oil globule diameter (0.165 ± 0.014 mm). The first division was observed approximately 45 min after fertilization. Blastula stage started after 4 h and the middle gastrula stage after 12:30 h. Early neurula was observed 17 h after fertilization. Cardiac beats and movements of the free embryonic tail were recorded after 30 h of incubation. Hatching occurred between 31 to 41 h and length of newly hatched larvae was 2.558 ± 0.051 mm. The embryonic development of this species is similar to previous studies regarding other marine fish. This study is the first report of embryonic development of A. scapularis, which is a valuable information that provide a baseline reference for the efforts for the culture of this species.